Comparison of Controlled Ovarian Stimulation Protocols on IVF Outcome in Normal and Poor Responders - Deniz Esinler; Fazilet Kübra Boynukalın; İbrahim Esinler; Tarık Aksu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Aim of this study is determining the influence of luteal long GnRH agonist and GnRH antagonist protocols on IVF/ICSI cycle outcome in group of patients considered “normal responder” and influence of luteal long GnRH agonist, microdose flare-up agonist and GnRH antagonist protocols on IVF/ICSI cycle outcome in a group of patients considered “poor responder”. STUDY DESIGN: This was a retrospective analysis performed in the Hacettepe University School of Medicine IVF Center, Ankara, from January 2005 to December 2007. Normal responders (first arm) were stimulated either with luteal long GnRH analogues, (193 patients and 300 cycles) or with GnRH antagonists (215 patients and 300 cycles). Poor responders (second arm) were stimulated either with luteal long GnRH analogues, (20 patients and 32 cycles), with GnRH antagonists (21 patients and 45 cycles) or microdose flare-up protocol (27 patients and 74 cycles). RESULTS: In the first arm; the clinical pregnancy, implantation and multiple pregnancy rates were comparable between the two groups in the first arm. In the second arm; clinical pregnancy, implantation and multiple pregnancy rates were comparable between three groups. CONCLUSION: There is insufficient evidence to recommend GnRH agonist or GnRH antagonist protocols for patients considered “normal’ and ‘poor responder’.